Identification of the porcine IG-DMR and abnormal imprinting of DLK1-DIO3 in cloned pigs - Li, Junliang; Yu, Dawei; Wang, Jing; Li, Chongyang; Wang, Qingwei; Wang, Jing; Du, Weihua; Zhao, Shanjiang; Pang, Yunwei; Hao, Haisheng; Zhao, Xueming; Zhu, Huabin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Abnormal gene imprinting is an important factor that leads to the abortion of cloned animals, and delta-like homolog 1 gene and the type III iodothyronine deiodinase gene (DLK1-DIO3) is an imprinted region related to growth and development. However, no systematic study has been performed reporting the imprinting status of the porcine DLK1-DIO3 region and the regulation of IG-DMR. The present study identified the location of IG-DMR and elucidated the imprinting status of the DLK1-DIO3 region. The porcine DLK1-DIO3 region was imprinted by SNP analysis of DLK1, GTL2, and DIO3 in crossbred pigs. IG-DMRs were mapped by homologous alignment and validated in sperm, oocytes, and fibroblasts, and IG-DMR was hypomethylated in parthenogenetic embryos. In addition, analysis of IG-DMR methylation and gene expression of the DLK1-DIO3 region were performed in fibroblasts, corresponding cloned embryonic fibroblasts, and parthenogenetic fibroblasts. The results showed that cloning resulted in aberrant hypermethylation of IG-DMR, and IG-DMR remained hypomethylated in parthenogenetic fibroblasts. Detailed analyses were performed in multiple tissues of wild-type neonatal pigs and cloned neonatal pigs. The results showed that the methylation of IG-DMR and the expression of most DLK1-DIO3 genes in the surviving cloned pigs were like those of the wild type, whereas the IG-DMR of the birth-dead cloned pigs were hypermethylated, and GTL2 expression was nearly undetectable. IG-DMR hypermethylation may suppress the expression of maternally imprinted GTL2. We localized the pig IG-DMR and analyzed the imprinting status of the DLK1-DIO3 region. Our study revealed that abnormal imprinting within the DLK1-DIO3 region affected the growth and development of cloned pigs and provided a theoretical basis for improving the cloning efficiency by gene editing to correct abnormal imprinting.